Use of Cabozantinib to Treat MET -amplified Pediatric Colorectal Cancer - Fukui, Sadahiro; Umeda, Katsutsugu; Kubota, Hirohito; Iwai, Atsushi; Akazawa, Ryo; Isobe, Kiyotaka; Tanaka, Kuniaki; Kouzuki, Kagehiro; Kawabata, Naoko; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; et al. (Journal of pediatric hematology/oncology, 2023)
Pediatric colorectal cancer (CRC) is extremely rare, with little information about genetic profiles compared with adult CRC. Here, a 13-year-old male with advanced CRC underwent cancer gene panel testing, which detected 4 genetic abnormalities ( MET amplification in addition to TP53 , SMAD4 , and CTNNA1 mutations) that might be associated with a poor prognosis. Based on high-level MET amplification, he received a multikinase inhibitor, cabozantinib, after failure of first-line and second-line chemotherapy, resulting in transient disease stabilization. Tailored targeted therapy based on molecular profiling can be an effective treatment strategy for rare cancers such as pediatric CRC.